Different levels of family ownership and dividend payout in the presence of growth opportunities - Irene, Wei Kiong Ting; Kweh, Qian Long; Norazlin, Ahmad; Paramanantham, Neshaleni S. (Inderscience Enterprises Ltd., 2021)
This study examines the family ownership, growth opportunities, and dividend payout of a sample consisting of 200 of the largest publicly listed companies in Malaysia from 2011-2016. Three main results emerge after controlling for firm and board characteristics as well as industry and year effects in various robustness checks. First, despite their positive impacts on dividend payout, family firms exhibit a lower dividend payout relative to net income. Second, growth opportunities increase the positive impacts of family ownership on dividend payout. A positive association between growth opportunities and dividend payout is also found. Third, the moderating effect of growth opportunities on the relationship between family ownership and dividend payout is present only in firms with family shareholdings, particularly those with high and medium ownership. These findings indicate varying dividend payout in the presence of growth opportunities for the different levels of family ownership.